Bronchopleural fistula spontaneous closure after SARS-CoV-2 infection - Ana Sara Gonçalves; Duarte Dória Freitas; Vítor Teixeira (The Egyptian Journal of Bronchology)
Background Bronchopleural fistula (BPF) is a rare cause of persistent air leak and is associated with high morbidity and mortality. BPF typically occurs after pulmonary surgery, but it can appear due to another etiology as in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Treatment options include both surgical and endoscopic procedures, depending on BPF diameters. BPF does not typically spontaneously undergo closure. Case report We describe a case of an English 78-year-old male patient, resident in Portugal, former smoker, with pulmonary fibrosis after coronavirus disease 2019 (COVID-19). He developed a central BPF with pneumothorax and pneumomediastinum, which spontaneously resolved after 2 months from the beginning of hospitalization. Conclusion This clinical case reports a different management of BPF, since spontaneous closure of BPF is barely described in the literature.